Action Video Games Improve Direction Discrimination of Parafoveal Translational Global Motion but Not Reaction Times. (October 2016) - Pavan, Andrea; Boyce, Matthew; Ghin, Filippo
Playing action video games enhances visual motion perception. However, there is psychophysical evidence that action video games do not improve motion sensitivity for translational global moving patterns presented in fovea. This study investigates global motion perception in action video game players and compares their performance to that of non-action video game players and non-video game players. Stimuli were random dot kinematograms presented in the parafovea. Observers discriminated the motion direction of a target random dot kinematogram presented in one of the four visual quadrants. Action video game players showed lower motion coherence thresholds than the other groups. However, when the task was performed at threshold, we did not find differences between groups in terms of distributions of reaction times. These results suggest that action video games improve visual motion sensitivity in the near periphery of the visual field, rather than speed response.